Keterlibatan Masyarakat Kelurahan Bansir Laut Mengelola Lingkungan Melalui Program Kota Tanpa Kumuh - Daim, Ahmad; Afandi, Afandi; Atmaja, Thomy Sastra (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2025)
This study examines the role of civic engagement in addressing urban slum issues, specifically through the Slum-Free City (KoTaKu) program in Bansir Laut Village, Pontianak. Using a qualitative approach, this research describes the various forms of citizen participation observed at every stage of the program, from planning to sustained implementation. The findings indicate that civic engagement is demonstrated through the proactive attitudes and behaviors of residents, supported by strong motivation and economic incentives. However, the program faced obstacles such as a lack of opportunity due to residents' busyness, social jealousy, and resistance from some community members. These challenges were successfully managed through incremental socialization, capacity building, and conflict resolution. Overall, civic engagement through the KoTaKu program proved to be a crucial step in creating a more livable and productive residential environment and improving community welfare. It is important to note that these findings are specific to Bansir Laut Village and may not be generalizable to other locations, as each community has its own unique social, economic, and dynamic characteristics.